Analisis Kemandirian Melalui Pola Belajar Pada Siswa Anak Tunggal Kelas V Sdn Purwokerto 01 Pantun - Nur Annisa Purwaningsih; Lintang Kironorati; Deka Setiawan (Mathematics Education Study Program, 2025)
This study aims to analyze the learning independence of fifth grade elementary school students, especially only children, in learning pantun material. Learning independence is the ability of students to plan, implement, and evaluate the learning process independently. This study uses a qualitative method with a case study approach, where data is collected through observation, in-depth interviews, and document analysis. The subjects of the study were fifth grade students who were only children. The results of the study showed that students' learning independence in understanding pantun material was influenced by internal factors such as motivation, self-discipline, and self-confidence, as well as external factors such as parental support and the learning environment. Although most students showed quite good independence, there were several obstacles such as dependence on parental assistance and lack of confidence in completing assignments. This study concludes that strengthening learning motivation and implementing learning strategies that encourage student independence are very necessary, especially in learning literature such as pantun.